Appearance of a genetically-based pollution resistance in a marine gastropod, Nucella lapillus, in southwest Brittany: a new case of Dumpton Syndrome - Huet, Martial; Le Goïc, Nelly; Gibbs, Pe (Journal of the Marine Biological Association of the United Kingdom, 2008)
International audience Most neogastropod species exhibit masculinization of the female when subject to tributyltin (TBT) pollution (a process known as 'imposex'). To date, the dog-whelk Nucella lapillus is seemingly unique in having a genetic deficiency (termed Dumpton syndrome or DS) that disrupts the development of normal male sex organs, its presence being readily recognizable by the underdevelopment, or non-development (aphally), of the penis, and incomplete formation (non-closure) of the vas deferens, causing a split prostate. In highly contaminated conditions, female carriers of DS can be identified by a lesser degree of masculinization (notably aphally): they escape sterilization caused by the advanced stages of imposex. To date, DS has only been reported in areas with high TBT pollution which induces sterilization of normal females (i.e. non DS-affected females). DS is now, for the first time, observed at some locations where present TBT levels are low and some normal females lack penis development. In such conditions it is not possible to discriminate normal from DS-affected females using aphally. As DS-affected females must be discarded from the calculation of the imposex bioindicators to monitor TBT pollution, indirect tools such as molecular probe are now needed to further survey those areas where DS and TBT pollution may interact as, for example, in south-west Brittany.